2020
DOI: 10.3389/fnbeh.2020.00001
|View full text |Cite
|
Sign up to set email alerts
|

Neural Code for Ambient Heat Detection in Elaterid Beetles

Abstract: Environmental thermal conditions play a major role at all levels of biological organization; however, there is little information on noxious high temperature sensation crucial in behavioral thermoregulation and survival of small ectothermic animals such as insects. So far, a capability to unambiguously encode heat has been demonstrated only for the sensory triad of the spike bursting thermo-and two bimodal hygrothermoreceptor neurons located in the antennal dome-shaped sensilla (DSS) in a carabid beetle. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 95 publications
(199 reference statements)
2
9
0
Order By: Relevance
“…Our data from the T-maze confirms that NMDARs in prefrontal excitatory cells are likely not necessary for spatial alternation performance, despite multiple experiments demonstrating the encoding of task-related information in the PFC 59 61 . The divergence between the results from the T-maze and the 5-CSWM task may be due to a difference in the neurophysiological underpinnings of DMTP and DNMTP WM in general, or between operant and spatial alternation-based maze assays, specifically.…”
Section: Discussionsupporting
confidence: 66%
“…Our data from the T-maze confirms that NMDARs in prefrontal excitatory cells are likely not necessary for spatial alternation performance, despite multiple experiments demonstrating the encoding of task-related information in the PFC 59 61 . The divergence between the results from the T-maze and the 5-CSWM task may be due to a difference in the neurophysiological underpinnings of DMTP and DNMTP WM in general, or between operant and spatial alternation-based maze assays, specifically.…”
Section: Discussionsupporting
confidence: 66%
“…Patki and colleagues showed that social defeat stress in rats reduced the level of CaMKIV in the hippocampus, leading to a depressive-like state in animals assessed by the sucrose preference test [ 17 ]. Similar results were observed both in the unpredictable chronic mild procedure and in the olfactory bulbectomized rats—depressive-like phenotype contributed to the decrease in the CaMKIV phosphorylation [ 137 , 174 ].…”
Section: Depression-like State In Rodentssupporting
confidence: 76%
“…The 3-hit model was based on a combination of genetic, environmental, and pharmacological risk factors. Each of these factors is not known to be sufficient per se to reproduce all aspects of the disorder, but are supposed to generate a more extensive pathology if they are associated [ 23 ]. Although a lot of studies showed a substantial role of genetic susceptibility on schizophrenia prevalence [ 24 , 25 ], whether one particular gene locus in the patients’ genome is essential remains unknown.…”
Section: Discussionmentioning
confidence: 99%